Practising in a post-truth world: Pandemic ethics can inform patient autonomy and clinical communication - J Fabian; H R Etheredge; C Lundgren; L Brannigan (South African Medical Journal, 2022)
The COVID-19 pandemic posed an unprecedented challenge to modern bioethical frameworks in the clinical setting. Now, as the pandemic stabilises and we learn to ‘live with COVID’, the medical community has a duty to evaluate its response to the challenge, and reassess our ethical reasoning, considering how we practise in the future. This article considers a number of clinical and bioethical challenges encountered by the author team and colleagues during the most severe waves of the pandemic. We argue that the changed clinical context may require reframing our ethical thought in such a manner as to adequately accommodate all parties in the clinical interaction. We argue that clinicians have become relatively disempowered by the ‘infodemic’, and do not necessarily have adequate skills or training to assess the scientific literature being published at an unprecedented rate. Conversely, we acknowledge that patients and families are more empowered by the infodemic, and bring this empowerment to bear on the clinical consultation. Sometimes these interactions can be unpleasant and threatening, and involve inviting clinicians to practise against best evidence or even illegally. Generally, these requests are framed within ‘patient autonomy’ (which some patients or families perceive to be unlimited), and several factors may prevent clinicians from adequately navigating these requests. In this article, we conclude that embracing a framework of shared decision-making (SDM), which openly acknowledges clinical expertise and in which patient and family autonomy is carefully balanced against other bioethics principles, could serve us well going forward. One such principle is the recognition of clinician expertise as holding weight in the clinical encounter, when framed in terms of non-maleficence and beneficence. Such a framework incorporates much of our learning and experience from advising and treating patients during the pandemic.